EVALUASI PELAKSANAAN PEMBELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL (IPAS) DALAM KURIKULUM MERDEKA SEKOLAH DASAR - Ramadhan, Wandri; Andi, Prastowo; Kathlyn Joyce , Nebres (Jurnal Gentala Pendidikan Dasar, 2023)
This research aims to reveal the evaluation of the implementation of Natural Science and Social Science (IPAS) learning in the fourth grade of elementary school within the Merdeka Curriculum, as well as the supporting factors and obstacles faced by teachers in implementing the learning process. The method used in this research is qualitative research with a descriptive study type. The research focuses on evaluating the CIIP model by Stufflebeam, which focuses on process evaluation. The object of this research is the learning process activities of fourth-grade students at Adisucipto 1 Public Elementary School in Yogyakarta, while the research subjects are fourth-grade teachers. Data collection techniques consist of observation, documentation, and interviews to strengthen the research results. The qualitative comparative technique is used for data analysis. The conclusion of this research is that the implementation of IPAS learning in the fourth grade of elementary school within the Merdeka Curriculum is in accordance with the process standards set in Permendikbudristek No. 16 of 2022. Supporting factors come from the leadership of the school principal, training and workshops related to the implementation of the Merdeka Curriculum, good student enthusiasm, support for school facilities and infrastructure in providing learning materials, teacher activities, the ability to use digital media such as computers and smartphones, and of course, the role of parents in their child's education. Meanwhile, the obstacles faced by teachers in implementation are that they are still new and have not fully understood the components and guidelines for learning and assessment in the Merdeka Curriculum.